Self-powered seesaw structured spherical buoys based on a hybrid triboelectric–electromagnetic nanogenerator for sea surface wireless positioning. Issue 2 (30th November 2021) - Hong, Hongxin; Yang, Xiya; Cui, Hui; Zheng, Duo; Wen, Haiyang; Huang, Ruiyuan; Liu, Liqiang; Duan, Jialong; Tang, Qunwei
Abstract : A self-powered seesaw-structured spherical triboelectric–electromagnetic hybrid nanogenerator buoy combining various working modes is presented for sea surface wireless positioning. Abstract : The rapid development of the Internet of Things has resulted in the harvesting of distributed sustainable energy receiving increasing attention. Recently, a study on triboelectric nanogenerators (TENGs) for collecting low-frequency and irregular-amplitude ocean wave energy has attracted significant interest. Herein, a self-powered seesaw-structured spherical triboelectric–electromagnetic hybrid nanogenerator (SSTE-HNG) combining various working modes is presented for harvesting wide-frequency wave energy from different directions and self-powered sea surface wireless positioning. The electrical output performances were systematically investigated and optimized via studying the effects of the configuration parameters, including the central slider mass, oscillation frequency, and swing amplitude of each module and the entire device; the instantaneous maximum output power densities of the origami zigzag-multilayer structured (OZ), freestanding layer rolling (FL), and electromagnetic generator (EMG) modules can reach 17, 4.8, and 9.8 W m −3, respectively, at an oscillation frequency of 0.7 Hz, and around 410 LEDs can be lit when operating the SSTE-HNG. Finally, the output voltage of the SSTE-HNG was stabilized using a transistor-controlled power management circuit for charging a 4.7 mF commercial capacitor in the range of 2.7 to 3.3 V; the seesaw-structured spherical buoy was used to drive a global positioning system (GPS) module for dynamic sea surface real-time wireless positioning, and our lab building on campus was successfully located upon installing the SSTE-HNG in a water tank. This study provides an ingenious design for achieving synchronized movements among hybrid effect/mode-based generators, and a self-powered buoy with a hybrid nanogenerator for sea surface wireless positioning was realized, which has the potential to be integrated with distributed electronics, such as sensors that collect sea surface meteorological information, in the future in the field of smart marine technology.